1998
DOI: 10.1523/jneurosci.18-11-04216.1998
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Divergence and Convergence in the Thalamocortical Projection to Monkey Somatosensory Cortex

Abstract: This study examined the extent of thalamocortical divergence as a potential determinant of activity-dependent representational plasticity in area 3b of adult monkey somatosensory cortex. Single or paired injections of anterogradely transported tracers, of varying anteroposterior extent, were made horizontally from behind in defined parts of the body representation in the ventral posterior lateral (VPL) and/or ventral posterior medial (VPM) thalamic nuclei, and the distribution and density of labeled thalamocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…The ventroposterior nucleus has been shown to have a somatotopic organization (Welker, 1974;Kaas et al, 1984;Kaas and Pons, 1988;Rausell et al, 1998). In the present study in particular, retrograde labeling was found in VPL after injections in areas PE and PEa dorsally.…”
Section: Topography Of Tc Projectionssupporting
confidence: 61%
“…The ventroposterior nucleus has been shown to have a somatotopic organization (Welker, 1974;Kaas et al, 1984;Kaas and Pons, 1988;Rausell et al, 1998). In the present study in particular, retrograde labeling was found in VPL after injections in areas PE and PEa dorsally.…”
Section: Topography Of Tc Projectionssupporting
confidence: 61%
“…These findings suggest that adult sprouting of corticocortical projections could contribute to the segregated pattern of activation reported here, although the most dramatic example of intracortical growth recorded in these studies projected only Ϸ50% of the more extensive nonactivated cortical distance observed (2 cm). The divergence of thalamocortical projections from a given representation within the ventral posterior nucleus has recently been demonstrated to extend further than previously appreciated, and these terminals typically coalesce into periodic densities (44). Whether this divergence can account for the cortical reorganization observed in the present study is an open question.…”
Section: Potential Mechanisms Underlying Cortical Reorganization Aftementioning
confidence: 55%
“…It is worth noting that in the spinal cord of monkeys, MOR, KOR, and DOR are approximately 68, 25, and 7% of the total binding sites, respectively, and that SNC80 is not able to stimulate [ 35 S]GTP␥S binding in this region (Lee et al, 2002). The thalamus is the major neural substrate modulating nociceptive signals from both spinothalamic and thalamocortical pathways (Bushnell et al, 1993;Craig et al, 1994;Shi and Apkarian, 1995;Rausell et al, 1998). Thus, it is highly possible that DOR agonists act as weak antinociceptive agents in monkeys due to the lower DOR density and consequent limited G protein activation in the spinothalamic pathway.…”
Section: Stimulation Of [ 35 S]gtp␥s Binding In Monkey Brainmentioning
confidence: 99%
“…In particular, the thalamus is the main neural substrate in nociceptive pathways and plays an integral role for both spinothalamic and thalamocortical pathways (Bushnell et al, 1993;Craig et al, 1994;Shi and Apkarian, 1995;Rausell et al, 1998). The aim of this present study was to measure the density of MOR, KOR, and DOR in the monkey cortex and thalamus.…”
mentioning
confidence: 99%